1993
DOI: 10.1111/j.1365-2052.1993.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphism of DQB and DRB class II genes of the ovine major histocompatibility complex

Abstract: Summary The ovine major histocompatibility complex (MhcOvar) class II region was investigated by Southern blot hybridizations using ovine probes specific for the second exons of Ovar‐DRB and Ovar‐DQB genes. Multiple bands were revealed when genomic DNA was digested with each of five restriction enzymes (Bam HI, Eco RI, Hin dIII, PvuII and TaqI), and successively hybridized with the two radiolabeled ovine probes. Restriction fragment length polymorphisms (RFLPs) were analysed in 89 sheep originating from six in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…Ballingall et C 1 OOfi Intrrntit ional Sor:ittty for Aninial Genetics, Ariirnd Genetics 27, 305-312 al. (1992) reported identical sequences for the normally highly polymorphic second exon from two DEB genes isolated from two unrelated sheep, supporting our result, but in contrast to the reports of Scott et al (1987), Grain et al (1993), Schwaiger et al (19933, and Dutia et al (1994). This would suggest that polymorphism at the ovine DRB requires further investigation.…”
Section: Polymorphism In the Mhcvvar Class Iiregionsupporting
confidence: 89%
See 2 more Smart Citations
“…Ballingall et C 1 OOfi Intrrntit ional Sor:ittty for Aninial Genetics, Ariirnd Genetics 27, 305-312 al. (1992) reported identical sequences for the normally highly polymorphic second exon from two DEB genes isolated from two unrelated sheep, supporting our result, but in contrast to the reports of Scott et al (1987), Grain et al (1993), Schwaiger et al (19933, and Dutia et al (1994). This would suggest that polymorphism at the ovine DRB requires further investigation.…”
Section: Polymorphism In the Mhcvvar Class Iiregionsupporting
confidence: 89%
“…Support for this can be derived from the human DR-region where polymorphism is greatest at the DRBl locus and other DRB loci show substantially less variability (Marsh & Bodrner 1993). although Grain et al (1993), used a very similar probe at higher stringency and reported polymorphism. Ballingall et C 1 OOfi Intrrntit ional Sor:ittty for Aninial Genetics, Ariirnd Genetics 27, 305-312 al.…”
Section: Polymorphism In the Mhcvvar Class Iiregionmentioning
confidence: 99%
See 1 more Smart Citation
“…growth, meat, wool and dairy production, fecundity and disease resistance). RFLP studies in sheep have identified variation in the major histocompatibility complex region (Chardon et al 1985;Grain et al 1993), the growth hormone locus (Byrne et al 1987;Parsons et al 1992a;Valinsky et al 1990), casein genes (DiGregorio et al 1991, immunoglobulin genes (Foley & Beh 1992), the scrapie-associated fibril protein gene (Hunter et al 1991), wool protein genes (Parsons et al 1992b(Parsons et al , 1993Rogers et at. 1993aRogers et at.…”
Section: Introductionmentioning
confidence: 99%
“…bovine (van der Poel et al 1990) and caprine (Mann et al 1993) MHC each contain a locus designated DY. Nucleic acid probe and oligonucleotide reagents have allowed the analysis of individual sheep MHC class I1 loci either by restriction fragment length polymorphism (RFLP) (Grain et al 1993) or polymerase chain reaction (PCR) (Schwaiger et al 1993). However, to study the distribution and function of sheep MHC class I1 proteins during the immune response, mAbs specific for the products of each of the expressed sheep MHC class I1 loci are required.…”
Section: Introductionmentioning
confidence: 99%